2005
DOI: 10.1007/s11274-005-2107-1
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Candida maltosa Hydrophobicity and Hydrocarbon Biodegradation

Abstract: The growth of Candida maltosa on hydrocarbons (dodecane and hexadecane) was influenced by adding various natural and synthetic surfactants. Microbial adhesion to the hydrocarbon was used to measure the surface cell hydrophobicity of the yeast, which in the presence of a synthetic surfactant correlated with the degree of hydrocarbon biodegradation. Non-ionic surfactants caused the highest degree of hydrocarbon biodegradation corresponding the lowest hydrophobicity. A different correlation was observed with natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
(18 reference statements)
3
10
0
Order By: Relevance
“…Evidently, biodegradation was followed by biomass formation, with the highest efficiency of 0.76 g, corresponding to the peak biodegradation rate. Such results are similar to the results from our previously conducted research (Chrzanowski et al 2006) using the same Candida maltosa EH 15 strain and rhamnolipid biosurfactant. Likewise, a turning point in hydrophobicity was observed at 150 mg/L surfactant concentration, related to the highest biodegradation rate and a maximum efficiency in biomass production.…”
Section: Influence Of Sdbs On Cell Surface Hydrophobicitysupporting
confidence: 90%
See 1 more Smart Citation
“…Evidently, biodegradation was followed by biomass formation, with the highest efficiency of 0.76 g, corresponding to the peak biodegradation rate. Such results are similar to the results from our previously conducted research (Chrzanowski et al 2006) using the same Candida maltosa EH 15 strain and rhamnolipid biosurfactant. Likewise, a turning point in hydrophobicity was observed at 150 mg/L surfactant concentration, related to the highest biodegradation rate and a maximum efficiency in biomass production.…”
Section: Influence Of Sdbs On Cell Surface Hydrophobicitysupporting
confidence: 90%
“…What is more, the modification of the cell envelope seems to play an important role in biodegradation of hydrocarbon pollutants. Our previously conducted research showed that anionic rhamnolipids have a tendency to adsorb on both yeast and bacterial cell walls (Chrzanowski et al 2006). Thus possible interactions between surfactants and microbial cells depend on the type of surfactant, type of substrate and are often individually connected to the type of a microorganism (Klotz 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Surface tension measurement proved that surfactants adsorb at the cell surface in respect to the surfactant type and its concentration. Research conducted with surfactants and microorganisms showed that rhamnolipids are strongly adsorbed at the cell surface of yeast, whereas saponin only marginally (Chrzanowski et al 2005a).…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus subtilis (Zhong et al, 2007). However, addition of surfactants such as rhamnolipids, Tween 80 and Triton X100 did result in consistent reduction of the CSH of bacteria with high cell hydrophobicity (Chrzanowski et al, 2006;Jana et al, 2000;Zhang and Miller, 1994). For microbial consortia isolated from soils contaminated with crude oil, addition of rhamnolipids and Triton X100 caused an increase in CSH of the hydrophilic consortia while a decrease in the hydrophobic consortia (Owsianiak et al, 2009).…”
Section: Introductionmentioning
confidence: 94%